Pengaruh Ukuran Venturi Karburator Terhadap Kinerja Mesin Honda Supra X - Muh Fadli; Risa Bernadip Umar; Ramli (Journal Teknik Dan Teknologi, 2025)
The use of motorcycles is currently increasing very rapidly. The impact is that fuel consumption is also increasing. Motorcycle technology is increasingly advanced and developing, from 2-stroke engines to 4-stroke engines, from carburetor fuel systems to injection. Motorcycles still use 2-stroke engines and carburetor systems. Inside the carburetor there is a venturi hole/pipe which has a very large effect on engine speed and fuel consumption according to the size of the venturi. From this background, an analysis of the effect of venturi size on fuel consumption can be carried out. The study was conducted with variations in carburetor venturi sizes of 18.3 mm, 18.8 mm and 22.8 mm with an engine speed of 4000 rpm (54 km / h) and premium fuel. Testing was carried out by measuring and recording the time of fuel consumption, then analyzing the standard venturi, enlarging and reducing the venturi diameter. The results of each carburetor venturi diameter on fuel consumption are each 18.3 mm venturi is 8.48 minutes, on the 18.8 mm venturi (standard) is 7.14 minutes and on the 22.8 mm venturi is 6.15 minutes. So that the reduction in the diameter of the carburetor venturi can reduce fuel consumption by 18.77% without reducing vehicle performance.